Fabrication of WO3 based nanocomposites for the excellent photocatalytic energy production under visible light irradiation. (16th November 2021) - Asiri, Abdullah M.; Nawaz, T.; Tahir, M.B.; Fatima, N.; Khan, Sher Bahadar; Alamry, Khalid Ahmad; Alfifi, Soliman Y.; Marwani, Hadi M.; Al-Otaibi, Maha M.; Chakraborty, Sudip
Abstract: Energy crisis and higher demands have lead scientists to search for economic and reliable sources of energy. In this research work, WO3 /BiVO4 (1%, 2%, 3% and 4%) composites are synthesized by using a facile hydrothermal method to produce hydrogen energy from biomass through photoelectrochemical cells. The photoanodes were made by using spin coating methods. The experimental results were analyzed by the SEM, XRD, UV–Vis, PL, and BET spectroscopic techniques. The XRD results showed that the material is crystalline and the average crystallite size is in the range of 50–55 nm, the SEM results showed that the materials have spheres-like nanostructures. The UV and PL results exhibited that absorption region increased and recombination rate decreased by adding BiVO4 up to 3%. The BET results showed the porosity of the material and exhibited that WO3 /BiVO4 (3%) has a large surface area (m 2 /g). The efficiency was analyzed by producing hydrogen energy and the results revealed that WO3 /BiVO4 (3%) showed the highest efficiency for producing hydrogen energy, which is 330.9 micro-mol.h −1 .g −1 . The material also showed excellent stability even after the third cycle. The extraneous efficiency caused due to redshift of the WO3 /BiVO4 (3%), high redox potential, high crystallinity, small bandgap and electronic interaction across the electrodes for the production of hydrogen gas fuel during efficient photocatalytic activity. Moreover, WO3 /BiVO4 (3%) is proved to be an active and favourable photocatalyst for the production of hydrogen energy from biomass/bio-wastes, which can be further utilized in various energy applications. Highlights: Nanocrystalline Hybrid BiVO4 /WO3 morphologies were synthesized by a simple hydrothermal approach. Visible-light hydrogen evolution from biomass was evaluated with prepared nanostructures. Photocatalysis via WO3 nanoparticles reinforced by both hydroxyl and superoxide radicals. High stability of the photocatalyst was observed for five consecutive cycles. Aspect ratio and surface properties were significant for efficient photocatalysis.